The GLP-1 receptor agonist liraglutide inhibits progression of vascular disease via effects on atherogenesis, plaque stability and endothelial function in an ApoE−/− mouse model - Gaspari, Tracey; Welungoda, Iresha; Widdop, Robert E; Simpson, Richard W; Dear, Anthony E (Diabetes & vascular disease research, 2013)
Liraglutide, a once-daily glucagon-like peptide-1 receptor (GLP-1R) agonist, has been approved as a new treatment for type 2 diabetes and is the subject of a clinical trial programme to evaluate the effects on cardiovascular disease and safety. The current study aimed to determine the in vivo effect of liraglutide on progression of atherosclerotic vascular disease in the apolipoprotein E-deficient (ApoE−/−) mouse model and identify underlying mechanisms responsible. Liraglutide treatment inhibited progression of early onset, low-burden atherosclerotic disease in a partially GLP-1R-dependent manner in the ApoE−/− mouse model. In addition, liraglutide treatment inhibited progression of atherosclerotic plaque formation and enhanced plaque stability, again in a partially GLP-1R-dependent manner. No significant effect of liraglutide on progression of late onset, high-burden atherosclerotic disease was observed. In addition, no significant endothelial cell dysfunction was identified in ApoE−/− mice with early onset, low-burden atherosclerotic disease, although significant prevention of weight gain was observed in liraglutide-treated mice using this dietary protocol. Taken together, these results suggest a potential role for liraglutide in the prevention and stabilisation of atherosclerotic vascular disease together with possible protection against major cardiovascular events.